Synthesis and characterization of activated carbon-supported magnetic nanocomposite (MNPs-OLAC) obtained from okra leaves as a nanocarrier for targeted delivery of morin hydrate - Öziç, Cem; Ertaş, Erdal; Baran, Mehmet Fırat; Baran, Ayşe; Ahmadian, Elham; Eftekhari, Aziz; Khalilov, Rovshan; Aliyev, Elvin; Yıldıztekin, Mahmut (Frontiers in Pharmacology, 2024)
Nanotechnology has emerged as a multifaceted subject that makes use of nanocarriers to integrate notions of alternative drug delivery systems. The method of encapsulating the drug molecule in a carrier, such as a magnetic nanoparticle, is a promising development that has the potential to deliver the medicine to the site where it is intended to be administered. Over the past few years, bioactive compounds have garnered a lot of attention in the realm of scientific research due to the fact that they are extremely low in toxicity and possess exceptional properties. Morin is a pentahydroxyflavone obtained from the leaves, stems, and fruits of various plantsmainly from the Moraceae family exhibiting diverse pharmacological activities such as anti-inflammatory, anti-oxidant, and free radical scavenging and helps treat diseases such as diabetes, myocardial infarction and cancer.In this study, we conducted the synthesis of a nanocomposite with magnetic properties by coating biocompatible activated carbon obtained from okra plant leaves with magnetic nanoparticles. Characterization of the synthesized activated carbon-coated magnetic nanocomposite was confirmed by Fourier transform infrared, scanning electron microscopy, dynamic light scattering, and zeta potential. The cytotoxic effects of the drug-loaded magnetic nanocomposite were examined in HT-29 (Colorectal), MCF-7 (breast), U373 (brain), T98-G (Glioblastoma) cancer cell lines, and human umbilical vein endothelial cells healthy cell line. We studied the loading and release behavior of morin hydrate in the activated carbon-coated magnetic nanocomposite. Activated carbon-coated magnetic nanocomposite carriers can show promising results for the delivery of Morin hydrate drugs to the targeted site.